Italian Environmental Historiography in the New Millennium: Four 'Short Histories'. (15th September 2019) - Palmieri, Walter
Between 2004 and 2015, after a decade of research and publications, four books on environmental history were published in Italy. The word 'short' appears in all their titles. Starting from this curious coincidence, this essay analyses, via the use of such books, the way through which the new historical paradigm has been addressed in Italy. It focuses on a wide range of issues, including epistemological definition, historical periodisation, fields of research, and the relationships between environmental history and other areas of history and natural sciences.